Prediction of nonresponsiveness to medium-dose intravenous immunoglobulin (1 g/kg) treatment: an effective and safe schedule of acute treatment for Kawasaki disease - Kyung Pil Moon; Beom Joon Kim; Kyu Jin Lee; Jin Hee Oh; Ji Whan Han; Kyung Yil Lee; Soon Ju Lee (Korean Pediatric Society, 2016)
PurposeMedium-dose (1 g/kg) intravenous immunoglobulin (IVIG) is effective in the majority of patients with Kawasaki disease (KD) but some patients who do not respond to medium-dose IVIG are at high risk for the development of coronary artery lesions (CALs). The purpose of this study was to identify the clinical predictors associated with unresponsiveness to medium-dose IVIG and the development of CALs.MethodsA retrospective study was performed in 91 children with KD who were treated with medium-dose IVIG at our institution from January 2004 to December 2013. We classified the patients into responders (group 1; n=68) and nonresponders (group 2; n=23). We compared demographic, laboratory, and echocardiographic data between the 2 groups.ResultsMultivariate logistic regression analysis identified 6 variables as predictors for resistance to medium-dose IVIG. We generated a predictive scoring system assigning 1 point each for percentage of neutrophils ≥65%, C-reactive protein≥100 mg/L, aspartate aminotransferase≥100 IU/L, and alanine aminotransferase≥100 IU/L, as well as 2 points for less than 5 days of illness, and serum sodium level≤136 mmol/L. Using a cutoff point of ≥4 with this scoring system, we could predict nonresponsiveness to medium-dose IVIG with 74% sensitivity and 71% specificity.ConclusionIf a patient has a low-risk score in this system, medium-dose IVIG can be recommended as the initial treatment. Through this process, we can minimize the adverse effects of high-dose IVIG and incidence of CALs.